Implementation of Ethnomathematics in Teaching Geometry Concepts in Elementary School: Systematic Literature Review - Marsya Aulia Nanda; Zahra Arin Luthfany; Ragil Dian Purnama Putri (Ar-Riyadhiyyat: Journal of Mathematics Education, 2026)
This study aims to identify forms of local cultural integration through ethnomathematics in teaching geometry concepts in elementary schools and analyze its impact on students conceptual understanding and learning motivation. The method used is a Systematic Literature Review (SLR) following the PRISMA flow, including definition, screening, and inclusion stages. Eight articles published from 2021 to 2025 were analyzed based on relevance and quality. The review shows that ethnomathematics effectively improves students conceptual understanding, motivation, and engagement. Cultural elements such as traditional games, artistic motifs, traditional foods, and traditional architecture are used as concrete media for learning geometry. The main challenges involve limited learning media and teachers’ ability to develop culture-based materials. Ethnomatematics supports contextual learning and aligns with the principles of the Merdeka Curriculum.